2018
DOI: 10.1002/jso.25286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed care on surgical management of patients with gastric cancer in a low‐resource setting

Abstract: Background: Gastric cancer is the fifth most common cancer in Eastern Africa. Diagnostic delays in low-resource countries result in advanced disease presentation. We describe perioperative management of gastric cancer in Rwanda. Methods: Retrospective review of records at three hospitals was performed to identify gastric adenocarcinoma cases from January 2012 – June 2016. Multiple perioperative and tumor-related variables were collected. Descriptive and bi-variate analyses were performed. Results: Final an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In-front surgery usually prevents mGC-related complications, such as bleeding, obstruction, or perforation [10,12,28]. Studies have shown that in-front palliative resection can prolong survival in select patients [10,12,29]. However, chemotherapy may be interfered with, or postponed due to, surgical morbidities or surgery-related worsening of the patient's general condition.…”
Section: Discussionmentioning
confidence: 99%
“…In-front surgery usually prevents mGC-related complications, such as bleeding, obstruction, or perforation [10,12,28]. Studies have shown that in-front palliative resection can prolong survival in select patients [10,12,29]. However, chemotherapy may be interfered with, or postponed due to, surgical morbidities or surgery-related worsening of the patient's general condition.…”
Section: Discussionmentioning
confidence: 99%
“…28 Palliative cancer surgeries may be particularly important in low resource settings due to a higher burden of advanced and therefore more symptomatic disease. 43 A study in India demonstrated feasibility and effectiveness of palliative operations for a variety of cancer patients, with the vast majority of patients endorsing subsequent symptomatic relief. 18 However, postoperative morbidity is an important consideration for any procedure, especially for patients with limited financial resources, health literacy, or access; weighing these risks and benefits necessitates a case-by-case determination and discussion with the patient and family.…”
Section: Prioritizing Quality Of Life Outcomesmentioning
confidence: 99%
“…Other proposed barriers to improved cancer surgery access, facilitation, and outcomes in low-resource settings include, but are not limited to: delayed presentation due to geographic isolation and transportation challenges 52 and sociocultural and sociopolitical factors, which ultimately increases care cost and complexity 53 ; unaffordable out-of-pocket costs, 54 which may disproportionately affect individuals in low-resource settings 55 ; and poor national cancer and cancer surgery registries, which may hinder accurate estimations of cancer surgery gaps and needs. 7,16,43 Broader health system gaps Indirect approaches, which emphasize external systems or policies that influence surgical cancer care, have also been a source of interest to researchers. For example, a study in Morocco sought to improve early cancer detection rates by providing point-of-care fecal immunochemical testing at primary health centers and offering colonoscopies for those who tested positive 56 ; however, only 62.6% of those who tested positive successfully underwent a subsequent colonoscopy, with many patients citing logistical and financial barriers to attending the follow-up procedure and appointments.…”
Section: Limited Resources and Perioperative Servicesmentioning
confidence: 99%